MODELING AND SIMULATION OF A BUCK CONVERTER CONTROLLED A SENSORLESS DC SERIES MOTOR (Journal of Engineering, 2010)
This paper presents modeling and simulation of a speed sensorless control for dc series motor driven by a buck converter through computation of the motor speed from converter output voltage and current. The system model considers the nonlinearity of the series motor magnetization characteristics including the variation of the field inductance with the motor current.